Comparison of Near Addition Value Prescription Methods for Myopic Children. Issue 1 (January 2016) - Yu, Xinping; Bao, Jinhua; Drobe, Björn; Lv, Wenhui; Wu, Ge; Xu, Jinling; Chen, Hao
ABSTRACT: Purpose: To compare personalized near addition values for myopic children that induce a reasonable phoria (Ph) (meeting Sheard's criterion) and induce a null lag of accommodation at near and to evaluate changes in these metrics after lens adaptation. Methods: Fifty-three myopic children participated in this study. Accommodative response, Ph, and fusional amplitudes (FAs) were measured at 33 cm through multiple addition lenses (0D, +1.00D, +1.50D, +2.00D, +2.50D, +3.00D). The adaptation effect on measured parameters was evaluated after 6 min of near work with each addition. The FA/Ph ratios were calculated for each addition and fitted using a rational function to obtain the optimal addition value satisfying Sheard's criterion (FA/Ph ≥ 2). Lag of accommodation change in association with addition value was assessed using linear regressions to obtain the addition values inducing a null lag. Results: Lag of accommodation (r = −0.987, p < 0.001) and Ph (r = −0.999, p < 0.001) decreased linearly with addition value. The 6-min adaptation induced a small but significant increase in accommodative lag and an exophoric shift (p < 0.05). Three FA/Ph patterns with respect to addition lenses were observed based on the near Ph: orthophoria/exophoria, low esophoria, and large esophoria. Addition values based on Sheard's criterion (mean ± SD, +2.16 ± 0.79D) were significantly lower than those based on null lag (+2.83 ± 0.44D, t = 19.86, p < 0.001). The FA/Ph ratio was less than 2.0 in 75.5% of subjects with additions determined through null accommodative lag. Additions determined through FA/Ph ≥ 2 induced a lag of accommodation of 0.38 ± 0.42D. Conclusions: Personalized near addition values using Sheard's criterion were lower than those obtained through null lag of accommodation. These values should allow a better binocular balance especially for exophoric children.